Practical guidance for the management of adults with immune thrombocytopenia during the COVID‐19 pandemic. (2nd June 2020) - Pavord, Sue; Thachil, Jecko; Hunt, Beverley J.; Murphy, Mike; Lowe, Gillian; Laffan, Mike; Makris, Mike; Newland, Adrian C.; Provan, Drew; Grainger, John D.; Hill, Quentin A.
Summary: This document aims to provide practical guidance for the assessment and management of patients with thrombocytopenia, with a particular focus on immune thrombocytopenia (ITP), during the COVID‐19 pandemic. The intention is to support clinicians and, although recommendations have been provided, it is not a formal guideline. Nor is there sufficient evidence base to conclude that alternative approaches to treatment are incorrect. Instead, it is a consensus written by clinicians with an interest in ITP or coagulation disorders and reviewed by members of the UK ITP forum.